Estratégias para otimizar a conservação da biodiversidade e serviços ambientais em paisagens produtivas e urbanas: trazendo ecologia à gestão territorial - Bálsamo, Silvana Masciadri (2016)
Increased production and land use intensification is one of the most important pressures on ecosystems and their goods and services, with great impact in Latin America in recent decades. Appropriate land management policies to balance production landscapes with biodiversity conservation contribute to achieve the goals of development and sustainability, also top of agendas in all countries of the region. Easily applicable tools are needed to find ways of rural and urban sustainability in the political system. Canelones department surrounds Montevideo –Uruguay’s capital— and has the highest concentration of farming areas compared to other departments. Accordingly, it is one of the departments with the greatest impact on natural ecosystems, due to anthropic activities and population growth, currently higher than national average figures. A state of environmental warning and strong pressures and threats to biodiversity was recognized, which currently extinct, endangered, or vulnerable species and several types of contamination detected. The need to bring ecology closer to land management is a key to achieve a sustainable approach, and a great challenge to settle agricultural production with the conservation of biodiversity and associated ecosystem services (EESS). This thesis therefore proposed the following objectives: 1. Develop a territorial management model for Canelones that maximizes biodiversity conservation in production landscapes, addressing different landscape scales, and proposing appropriate environmental political and administrative management; 2. To investigate whether the productive land uses proposed by the Project AGUT: Fitness General Land Use (2010), are in accordance with the model 10:20:40:30 (Ch. 1), and if it is aligned with the objectives of sustainable development set out in the environmental agendas of the country; 3. Test if land surface of EESS mapped in Soutullo et al (2012) matches with the model, and estimate through the sale value of the land in the market, the cost to optimize the conservation of biodiversity and EESS in three scenarios: the model 10:20:40:30, AGUT (2010), and land surface of EESS of high conservation priority. Chapter 1 compared the current land uses (OPP 2010) with the model proposed by Smith et al. (2013), which suggests a general framework to maximize the retention of biodiversity in an agricultural landscape: the 10:20:40:30 guide. A GIS was elaborated offering tools to apply in land planning at Canelones, in landscapes scales defined by political management boundaries. The natural cover showed significant values lower the model, reflecting the pressure on natural ecosystems that exists in all landscape scales analyzed. The urgent challenge is increasing the natural soil surface. The potential management at different scales allows each locality to apply their strategies to recover natural soil, using natural parks, artificial lakes restoration, recuperation of riparian forests and wetlands. It also provides a planning framework for public and administrative policies. Chapter 2 compared productive land use projected by AGUT (2010) reclassified on intensive, moderate, low and natural, and test if it fits the model (Ch. 1). A GIS was developed as a tool for land planning. The results showed that the projection AGUT ensures no sustainability at all. The differences between both were significant, and the minimum of natural soil needed to promote conservation of biodiversity and associated EESS are not preserved. It would increase pressure on water resources and biological corridors of fluvial forest and riparian wetlands, intensifying land use in the entire territory, leading to a homogenization of the productive landscape through intensive and moderate land uses, and eliminating the possibilities of damping and environmental restoration, since no low land uses are proposed and natural cover is taken to a minimum. With this intensive productive landscape proposal, the objectives of productive and sustainable development posed by AGUT project would not be achieved, nor the guidelines to the same purpose planned by departmental guidelines in Canelones, and also is not in line with the national legislation or national and international agreements that Uruguay has assumed as environmental targets to be attained in the millennium development goals. Chapter 3 contrasted if the land area of EESS, with high priority conservation (Soutullo et al. 2012) matches the 10 % of natural cover of the model (Ch. 1). Moreover, through the market value of the land for sale, an assessment of costs was made to achieve the objectives of conservation and sustainability for Canelones, recovering it from the current scenario (Ch. 1), from AGUT (2010) (Ch. 2) and from EESS land cover. In the compared scenarios, at the departmental level, the EESS soil is greater (16,2%) than natural cover of the model (10%), although the results was wide-ranging in the other land scales analyzed. The 10% conservation of natural soil could arise as a conservation objective in the short and medium time. Moreover, reaching the EESS land cover could be a long-term goal, implementing management measures of that high priority surface to conserve. Economic valuation of natural cover of EESS provides opportunities to internalize and display costs in the economy. Indeed, cost estimates of achieving the objectives of 10% natural soil from the current scenario (OPP 2010), are less than the costs to get from the scenario posed by AGUT (2010), although higher are those to achieve the objectives of EESS land conservation. The balance between productive and sustainable systems, conservation of biodiversity and water resources of Canelones, should consider including more precisely in territorial policies a balance between them. The model 10:20:40:30 proposed an optimization of production and conservation objectives, ensuring minimal natural cover, and a percentage of buffer land cover, as moderate and low, to maintain connectivity and reduce fragmentation (Ch. 1). Analyzed landscape scales also offer opportunities in regional planning from different administrative areas, providing more variety of occasions for management of natural and cultural heritage of Canelones. Moreover, the academic and social scenario is very favorable, and although there are usage conflicts and anthropic impacts, society is increasingly receptive to environmental issues. Their participation is provided as fundamental and necessary to achieve sustainability goals in the long term.